2010
DOI: 10.1200/jco.2010.30.6423
|View full text |Cite
|
Sign up to set email alerts
|

Induction Docetaxel, Cisplatin, and Cetuximab Followed by Concurrent Radiotherapy, Cisplatin, and Cetuximab and Maintenance Cetuximab in Patients With Locally Advanced Head and Neck Cancer

Abstract: A B S T R A C T PurposeWe incorporated cetuximab, a chimeric monoclonal antibody against the epidermal growth factor receptor (EGFR), into the induction therapy and subsequent chemoradiotherapy of head and neck cancer (HNC). Patients and MethodsPatients with locally advanced HNC, including squamous and undifferentiated histologies, were treated with docetaxel 75 mg/m 2 day 1, cisplatin 75 mg/m 2 day 1, and cetuximab 250 mg/m 2 days 1, 8, and 15 (after an initial loading dose of 400 mg/m 2 ), termed TPE, repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(90 citation statements)
references
References 30 publications
3
84
1
2
Order By: Relevance
“…Response rate after induction therapy with cetuximab containing regimens has been between 66 % to 77%. Response rate after induction chemoterapy with docetaxel or paclitaxel and cetuximab followed by chemoradiation has been 77 to 100% with acceptable toxicity (24)(25)(26)(27)(28). There is no phase III study to compare concomitant chemoradiation with bioradiation, directly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Response rate after induction therapy with cetuximab containing regimens has been between 66 % to 77%. Response rate after induction chemoterapy with docetaxel or paclitaxel and cetuximab followed by chemoradiation has been 77 to 100% with acceptable toxicity (24)(25)(26)(27)(28). There is no phase III study to compare concomitant chemoradiation with bioradiation, directly.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that sequentional modality containing cetuximab is safe with high response rate and promising survival (26). survival and overall survival were 70% and 74%, respectively (27). The randomized phase II study (TREMPLIN study) was designed to compare the efficacy and safety of induction chemotherapy followed by chemoradiotherapy or bioradiotherapy for larynx preservation.…”
Section: Sequential Modalities (Table 3)mentioning
confidence: 99%
“…The University of Pittsburgh group has published results evaluating IC consisting of docetaxel, cisplatin, and cetuximab (TPE) followed by RT, cisplatin, and cetuximab (XPE) which was followed by maintenance cetuximab for 6 months in 39 patients (Argiris et al, 2010). Among 37 evaluable patients, the overall objective response was 86% after IC and 100% after CRT.…”
Section: Cetuximab As Part Of Induction Chemotherapy (Ic) Regimensmentioning
confidence: 99%
“…Similar LITT studies have followed with a translational experimental model combining intratumor cisplatin with Nd:YAG laser for thermal ablation of recurrent and advanced head and neck cancer (Paiva et al, 1998b;Graeber et al, 1999). Despite important advances in current therapy with surgery, radiation, and chemotherapy, nearly one half of all head and neck cancer patients will develop persistent or recurrent disease (Adelstein, 1998;Argiris et al, 2010;Bonner et al, 2006;Correa and Burkey, 1999;Weisman and Robbins, 1998). Head and neck tumors are an excellent disease model for testing intratumor chemotherapy and laser because of their accessibility for surgery and their loco-regional biological behavior .…”
Section: Photo-chemical and Photo-thermal Activation Of Anti-cancer Dmentioning
confidence: 99%
“…Studies have shown that even more effective eradication of head and neck cancer is possible by combining LITT with local, intratumor injections of CDDP (Clayman et al, 1999). Currently, cisplatin or cisdiamminedichloroplatinum (CDDP) are the most commonly used chemotherapeutic agents for head and neck cancer (Argiris et al, 2010;Bonner et al, 2006;Forastiere et al, 2006). technology.…”
Section: Clinical Relevance Of Laser and Cisplatin In Photo Chemotherapymentioning
confidence: 99%